Floristic Diversity of Vascular Plants in Community Managed Forest of Sankhu village, Lalitpur District, Nepal (Patan Pragya, 2023)
The plant diversity of an area reveals its biodiversity, usage patterns, and conservation status which play a significant role in shaping the country's conservation plans and strategies. The present study aims to describe the vascular plants diversity of Lakuribhanjyang community forest in Lalitpur, Central Nepal. This community forest comprises an area of 43.5 hectares and the altitude ranged 1763m to 1833m asl. The study recorded 111 plant species from 102 genera and 64 families in the Lakuribhanjyang community forest. Among the documented species, trees (49 species) were dominantly followed by herbs (33 species), shrubs (18 species), and climbers (11 species). A total of 90 dicots, 7 monocots, 4 gymnosperms, and 10 pteridophytes were documented. Plants from the Moraceae family (6 spp.) dominated the research area, followed by plants from Asteraceae, Fabaceae, Poaceae and Rosaceae each with 5 species each. Ageratina adenophora, Ageratum conyzoides, Alternanthera philoxeroides, Bidens pilosa, Senna tora and Lantana camara were the invasive plant species that were found in the study area. Similarly, Choerospondias axillaris, Dioscorea deltoidea, Lithocarpus fenestratus, Senegalia catechu, Valeriana jatamansi and Zanthoxylum armatum were the endangered and threatened vascular plants listed in Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) that was found in this region.